Creating a Master's Degree in systems integration: capturing and embedding industry knowledge. (28th December 2009) - Campbell, Alistair; Cropley, David
Australia has a skills shortage in the defence industry. Growing demand for complex defence systems highlighted the need for additional systems engineers and systems integration specialists. This is compounded by sustained growth in Australia's resources sector, and competition for engineering professionals. The Skilling Australia's Defence Industry (SADI) initiative provides significant funding for new skills activities. This paper describes one such activity; the creation of a Masters degree in Military Systems Integration (MSI). Designing and implementing the program required some novel educational approaches, to capture the value of industry experience, and integrate critical but elusive aspects that require tacit knowledge transfer.